1967
DOI: 10.1302/0301-620x.49b4.698
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral Calcinosis

Abstract: 1. Tumoral calcinosis and lipocalcinoma-granulomatosis are synonymous terms for the same entity. 2. The condition justifies inclusion as an important type of calcinosis and is to be differentiated from calcinosis universalis and calcinosis circumscripta. 3. It occurs during the first or second decades, large dense nodular masses forming in the periarticular tissues at the hips, shoulders and elbows. Smaller masses may have a wider distribution. 4. It has been reported to be a metabolic disease of obscure et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

1970
1970
2000
2000

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Hidden loci may be detected by conventional X-ray or a technetium scan. The location of lesions in some of our cases such as the face, elbows, knees and fingers was quite unusual 9 Secondary infections in our cases were common but none with severe generalized deterioration, as has been reported, probably due to long-standing inflammation [22]. Two of our boys had a lesion on the tibia, one showing cortical hyperostosis with hyperphosphataemia.…”
Section: Discussionsupporting
confidence: 69%
“…Hidden loci may be detected by conventional X-ray or a technetium scan. The location of lesions in some of our cases such as the face, elbows, knees and fingers was quite unusual 9 Secondary infections in our cases were common but none with severe generalized deterioration, as has been reported, probably due to long-standing inflammation [22]. Two of our boys had a lesion on the tibia, one showing cortical hyperostosis with hyperphosphataemia.…”
Section: Discussionsupporting
confidence: 69%
“…An apparent inherited disorder of phosphate and vitamin D metabolism has also been described [8,19,28,34,37,38,48]. Trauma has been implicated as a cause in selected patients [5,10,15,30,36,39,42,44]. Although surgical specimens of the patients reported here revealed findings typical of tumoral calcinosis, the patients' age and race are atypical, and the lesions were solitary, unusually small, and in an atypical location.…”
Section: Discussionmentioning
confidence: 72%
“…Tumoral calcinosis in the presence of a normal circulating phosphate concentration is, however, the rule rather than the exception [4,6,13,17,39,43]. Hyperphosphatemia is reported to occur in only one-third of patients, and in them tumoral calcinosis may be a distinct clinical entity [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a long time the two above entities have been considered different subgroups of calcinosis (Danowski 1962). Subsequent study of various cases indicated that tumoral calcinosis and lipocalcinomagranulomatosis were the same conditions (Smit & Schmaman 1967). …”
mentioning
confidence: 99%